Improving Science Learning Outcomes On Special Characteristics Of Living Animal Creatures Through The Jigsaw Method In Class Vi Students Of SDN 019 Tanjung Sawit, Tapung District - Saminem, Saminem (Jurnal Ilmiah Mandala Education (JIME), 2023)
The aim of this research is to determine the improvement in science learning outcomes regarding special characteristics of living animals using the jigsaw method in class VI students at SDN 019 Tanjung Sawit, 2022. This type of research is Classroom Action Research (PTK). The research subjects are class VI students. SDN 019 Tanjung Sawit has 16 students consisting of 6 boys and 10 girls. Based on the results of the research, the researchers concluded that the jigsaw method could improve learning achievement in class VI students on the special characteristics of living animals at SDN 019 Tanjung Sawit for the 2022/2023 academic year. The average class score increased from 65 (pre-cycle) to 85 and this PTK was considered successful. To all teachers at SDN 019 Tanjung Sawit, Tapung District, in an effort to improve students' understanding of learning, they can use the jigsaw method with the CTL (Contextual Teaching Learning) approach in the teaching and learning process